Convergence estimates for the acoustic scattering problem approximated by NURBS - Karafiat, Andrzej (Computer Assisted Methods in Engineering and Science, 2013)
The paper contains some estimates of an approximation to the solution of the problem of acoustic waves's scattering by an elastic obstacle in two dimensions. The problem is approximated by the isogeometric adaptive method based on the known NURBS functions. The estimates show how the error of an approximation depends on the size of intervals and the degree of functions.